Polyhedral silver clusters as single molecule ammonia sensor based on charge transfer-induced plasmon enhancement - Chen, Jiu-Huan; Cheng, Xin-Lu (Chinese physics B, 2023)
The unique plasmon resonance characteristics of nanostructures based on metal clusters have always been the focus of various plasmon devices and different applications. In this work, the plasmon resonance phenomena of polyhedral silver clusters under the adsorption of NH 3 , N 2 , H 2 , and CH 4 molecules are studied by using time-dependent density functional theory. Under the adsorption of NH 3 , the tunneling current of silver clusters changes significantly due to the charge transfer from NH 3 to silver clusters. However, the effects of N 2 , H 2 , and CH 4 adsorption on the tunneling current of silver clusters are negligible. Our results indicate that these silver clusters exhibit excellent selectivities and sensitivities for NH 3 detection. These findings confirm that the silver cluster is a promising NH 3 sensor and provide a new method for designing high-performance sensors in the future.